VALUE RELEVANCE LABA DAN ARUS KAS DENGAN PENDEKATAN PORTFOLIO-RETURN - Dwi Fitri Puspa (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2006)
The value relevance literature is related to the usefulness of financial statement asan information in equity valuation. This study is conducted to measure the value relevance of earnings and cash flows by using the portfolio return approach. the study is to examine whether the proportion of all information in security returns that are captured by the accounting-based measures in earnings information are higher than in cash flows information. The sample covers listed companies in Jakarta Stock Exchange in 1991. The number of samples that fulfills the criteria are 79 companies and the sample period was 1996 to 2001. The findings indicate that the value relevance of accounting information in terms of earnings and cash flows is value-relevant. Furthermore the findings show that the value relevance of earnings information is higher than that of cash flows information. The knowledge of the change in earnings (cash flows) earns 45.68% (16.89%) of these returns.Keywords: value relevance; portfolio return; earnings; cash flows